Applications of Cryogenic Electron Microscopy in Biomineralization Research. (May 2022) - Lei, C.; Wang, Y.H.; Zhuang, P.X.; Li, Y.T.; Wan, Q.Q.; Ma, Y.X.; Tay, F.R.; Niu, L.N.
Biological mineralization is a natural process manifested by living organisms in which inorganic minerals crystallize under the scrupulous control of biomolecules, producing hierarchical organic-inorganic composite structures with physical properties and design that galvanize even the most ardent structural engineer and architect. Understanding the mechanisms that control the formation of biominerals is challenging in the biomimetic engineering of hard tissues. In this regard, the contribution of cryogenic electron microscopy (cryo-EM) has been nothing short of phenomenal. By preserving materials in their native hydrated status and reducing damage caused by ion beam radiation, cryo-EM outperforms conventional transmission electron microscopy in its ability to directly observe the morphologic evolution of mineral precursor phases at different stages of biomineralization with nanoscale spatial resolution and subsecond temporal resolution in 2 or 3 dimensions. In the present review, the development and applications of cryo-EM are discussed to support the use of this powerful technique in dental research. Because of the rapid development of cryogenic sample preparation techniques, direct electron detection, and image-processing algorithms, the last decade has witnessed an exponential increase in the use of cryo-EM in structural biology and materials research. By amalgamating with other analytic techniques, cryo-EM may be used for qualitative and quantitative analyses of the kinetics and thermodynamic mechanisms in which organic macromolecules participate in the transformation of mineral precursors from their original liquid state to amorphous and ultimately crystalline phases. The present review concentrates on the biomineralization of calcium phosphate mineral phases, while that of calcium carbonate, silica, and magnetite is only briefly mentioned. Bioinspired organic matrix–mediated inorganic crystallization strategies are discussed from the perspective of tissue regeneration engineering.